Production Of Cold And Hot Press Of Nigella Sativa L Oil And Meal Using Screw Press - Silvia, Deli (2011)
Effects of physical parameters of a screw press machine on oil yield of N. sativa seeds were studied using a KOMET Screw Oil Expeller. Different nozzle size (6, 10, and 12 mm), extraction speed (21, 54, 65 and 98 rpm) and diameter of shaft screw (8 and 11 mm) pressed at 60 °C were applied in this study. Highest percentage of oil yield recorded was at combination of shaft screw with diameter of 8 mm, rotational speed at 21 rpm and nozzle size of 6 mm. Oil yields were higher at 50 °C (cold press) (22.68 %) and lower at 100 °C (hot press) (15.21 %). Percentage meal yield of N. sativa seeds were lower at 50 °C (73.48 %) and higher at 100 °C (80.50 %). The oil and meal yield were significantly different (p<0.05) in different temperatures.